PENENTUAN AREA BERISIKO ASPEK DRAINASE KOTA CIMAHI BERDASARKAN PEDOMAN STRATEGI SANITASI KOTA 2018 - Utami, Elvira Rizqita; Juwana, Iwan (CREATIVE RESEARCH JOURNAL, 2020)
Cimahi City is one of the cities that participated in the Accelerated Habitation Sanitation Development Program in 2011. This was done because the Cimahi City Government realized that the sanitation conditions in Cimahi City were still of concern. In 2015, the coverage of drainage system services reached 89.87%. Meanwhile, inundation and flood area in 2018 in Cimahi City reached 36.4 hectares or equal to 0.76% of the total area of Cimahi City. Inundation and floods that occur resulting in displaced residents as well as financial losses. Based on the following problems, this study was conducted to calculate the level of risk in each urban village in Cimahi City. The level of risk is expressed in scores ranging from 1 - 4. A score of 1 means very low risk, a score of 2 means low risk, a score of 3 means high risk, and a score of 4 means very high risk. Determination of risk scores involves exposure factors and impact factors Exposure factors consist of inundation area percentage, sanitation risk index (IRS) score based on EHRA, and OPD perceptions. While the impact factors consist of population, population density, poverty rate, and urban / rural function.